Haematoxylon campechianum extract ameliorates neuropathic pain via inhibition of NF-κB/TNF-α/NOX/iNOS signalling pathway in a rat model of chronic constriction injury - Sobeh, Mansour; Mahmoud, Mona F.; Rezq, Samar; Abdelfattah, Mohamed A. O.; Mostafa, Islam; Alsemeh, Amira E.; El-Shazly, Assem M.; Yasri, Aziz; Wink, Michael (Biomolecules, 2020)
In this study, the phytochemical composition and the possible prophylactic effects of an aqueous ethanol extract of Haematoxylon campechianum flowers (HCF) on peripheral neuropathic pain in a chronic constriction injury (CCI) rat model are investigated. Rats with induced CCI were subjected to neuropathic pain behaviour tests and evaluated by chemical, thermal, and mechanical sensation tests and functional recovery of the brain stem and sciatic nerve at 7- and 14-day intervals. The effect of the extract on acute pain and inflammation is also investigated. The extract exerted both peripheral and central analgesic and anti-inflammatory properties in addition to antipyretic effects that are clear from targeting COX, LOX and PGE. It was found that CCI produced significant thermal and mechanical hyperalgesia, cold allodynia and deleterious structural changes in both sciatic nerve and brain stem. Treatments with HCF extract significantly improved cold and thermal withdrawal latency, mechanical sensibility and ameliorated deleterious changes of sciatic nerve and brain stem at different dose levels. The extract also ameliorated oxidative stress and inflammatory markers in brain stem and sciatic nerve. It suppressed the apoptotic marker, p53, and restored myelin sheath integrity. The effects of HCF extract were more potent than pregabalin. Fifteen secondary metabolites, mainly gallotannins and flavonoids, were characterized in the extract based on their retention times and MS/MS data. The identified phenolic constituents from the extract could be promising candidates to treat neuropathic pain due to their diverse biological activities, including antioxidant, anti-inflammatory and neuroprotective properties.